2020
DOI: 10.1002/prep.201900425
|View full text |Cite
|
Sign up to set email alerts
|

Ignition and Extinction of n‐Butyl Nitroxyethylnitramine‐Plasticized Polyethylene Glycol Propellants

Abstract: The ignition and extinction of n‐butyl nitroxyethylnitramine (BuNENA)‐plasticized polyethylene glycol (PEG) propellants were investigated with respect to the concentration of binder and the ratio of plasticizer to polymer (pl/po). A distinctive change in the ignition delay time (tign) of the propellants was found at a low pressure of 0.03 MPa, where tign increases as the binder concentration increases from 24 % to 32 % and decreases when the pl/po ratio reaches from 1 to 6. The kinetic analysis shows that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…[21][22][23] However, the practical application of a triazole-cured binder system is inhibited by unsatisfied mechanical properties. 24,25 Unlike the isocyanates curing system, the rigid triazole rings failed to induce the aggregation of hard segments to form a micro-phase separation structure, 26 due to insufficient intermolecular force. 27,28 Furthermore, the GAP-based triazole-cured binder system suffers from uncontrollable reaction equivalent because the molecular chain contains many CH 2 N 3 side groups, 29 and the preformed rigid triazoles had great spatial occupancy which hindered the formation of nearby triazoles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] However, the practical application of a triazole-cured binder system is inhibited by unsatisfied mechanical properties. 24,25 Unlike the isocyanates curing system, the rigid triazole rings failed to induce the aggregation of hard segments to form a micro-phase separation structure, 26 due to insufficient intermolecular force. 27,28 Furthermore, the GAP-based triazole-cured binder system suffers from uncontrollable reaction equivalent because the molecular chain contains many CH 2 N 3 side groups, 29 and the preformed rigid triazoles had great spatial occupancy which hindered the formation of nearby triazoles.…”
Section: Introductionmentioning
confidence: 99%
“…The GAP binder system can further form a triazole‐based network via alkyne‐azide Huisgen cycloaddition, 19,20 which is insensitive to humidity, simpler, and faster than the traditional isocyanates curing system 21–23 . However, the practical application of a triazole‐cured binder system is inhibited by unsatisfied mechanical properties 24,25 . Unlike the isocyanates curing system, the rigid triazole rings failed to induce the aggregation of hard segments to form a micro‐phase separation structure, 26 due to insufficient intermolecular force 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is no relevant research on the rate constants for the decomposition of alkyl-NENAs that contain both of nitrate ester and nitramine. Recently, an interesting work demonstrated that the NEPE propellants plasticized by BuNENA resulted in a high pressure deflagration limit (PDL) of 2.28 MPa and a long ignition delay time in vacuum [11]. It was surmised that a very slow reaction involving NO, which is produced by the reduction of NO 2 , would play a significant role in ignition delay and combustion characteristics.…”
Section: Introductionmentioning
confidence: 99%